A study on factors that lead to job satisfaction among academic staff at AIMST University / Siti Faridah Jaafar and Norsidah Farhana Marzukhi - Jaafar, Siti Faridah; Marzukhi, Norsidah Farhana (2018)
This research was conducted to study the factors that lead to job satisfaction among academic staff in private university. This study conducted in order to determine which factors need to be highlight by private university to ensure that the employees have high level of job satisfaction toward the institution and increase the commitment in order to remain in the institution. In this study, the quantitative research method had been used in which relies on the primary data from a survey which involve the academic staff at AIMST University in Bedong, Sungai Petani, Kedah. The total sample size for this study is 169 respondents. This study had conducted on this amount of sample sizes and the data had been collected in November 2018. The analysis on the findings for this study had managed to answer all objectives stated. From the findings, the researchers have found there is relationship between the all independent variables and job satisfaction among academic staff. The independent variables showed that there is a significant relationship between variables. Therefore, it can be concluded that there was relationship between job satisfaction among academic staff at AIMST University with all the variables.